Periodontal ligament tissues support neutrophil differentiation and maturation processes - Villagómez-Olea, Guillermo; Uribe-Querol, Eileen; Marichi-Rodríguez, Francisco Javier; Meléndez-Zajgla, Jorge; Alvaréz-Pérez, Marco Antonio; Rosales, Carlos (Frontiers in Immunology, 2024)
IntroductionPeriodontal ligament is the soft connective tissue joining the roots of teeth with alveolar bone. The periodontal ligament presents significant cellular heterogeneity, including fibroblasts, endothelial cells, cementoblasts, osteoblasts, osteoclasts, and immune cells such as macrophages and neutrophils. These cells have crucial roles for periodontium homeostasis and function. However, certain cell types, such as neutrophils, remain poorly characterized in this tissue, despite their natural abundance and relevance in processes and diseases affecting the periodontal ligament.MethodsIn order to characterize neutrophils present in periodontal ligament, and get some insight into their functions, single-cell RNA sequencing data from published reports was analyzed to integrate and create a comprehensive map of neutrophil heterogeneity within the murine periodontal ligament under steady-state conditions.ResultsFour distinct neutrophil populations were identified based on their unique transcriptional signatures. Comparison and trajectory analysis revealed that these populations represent discrete stages of neutrophils undergoing maturation. These neutrophil populations were also classified, based on their granule content-associated signatures, as azurophil, specific, a transitional stage between specific and gelatinase (specific/gelatinase), and gelatinase. This reflects the sequential order of granule formation during neutrophil development (granulopoiesis) in the bone marrow.DiscussionTogether, our findings indicate that the periodontal ligament may serve as a microenvironment where the ordered and sequential maturation of neutrophils takes place. This suggests that similarly to other niches, the murine periodontal ligament can support, to some extent, hematopoietic processes such as granulopoiesis.